Synthesis and Antimicrobial Activity of 1-Substituted Phenyl-3-substituted Phenyl-4-[(3,4,5-trimethoxy)-5-benzyl]-4-aminopyrimidine Formazans - Narendra Babu, A.; Rao Nadendla, Rama (Asian Journal of Chemistry, 2010)
A series of 15 novel 1-substituted phenyl-3-substituted phenyl-4-[(3,4,5-trimethoxy)-5-benzyl]- 4-amino pyrimidine formazans [2a-2o] were synthesized from trimethoprim. All the compounds were characterized by analytical and spectral analysis. The antibacterial and antifungal activities were screened for all the compounds. The synthesized compounds were found to have significant effect against the tested organisms.